Bioorthogonal Catalytic Activation of Platinum and Ruthenium Anticancer Complexes by FAD and Flavoproteins. (15th February 2018) - Alonso‐de Castro, Silvia; Cortajarena, Aitziber L.; López‐Gallego, Fernando; Salassa, Luca
Abstract: Recent advances in bioorthogonal catalysis promise to deliver new chemical tools for performing chemoselective transformations in complex biological environments. Herein, we report how FAD (flavin adenine dinucleotide), FMN (flavin mononucleotide), and four flavoproteins act as unconventional photocatalysts capable of converting Pt IV and Ru II complexes into potentially toxic Pt II or Ru II −OH2 species. In the presence of electron donors and low doses of visible light, the flavoproteins mini singlet oxygen generator (miniSOG) and NADH oxidase (NOX) catalytically activate Pt IV prodrugs with bioorthogonal selectivity. In the presence of NADH, NOX catalyzes Pt IV activation in the dark as well, indicating for the first time that flavoenzymes may contribute to initiating the activity of Pt IV chemotherapeutic agents.